Comparison of Turkish and Indonesian secondary mathematics curricula; reflection of the paradigms - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
The aim of this study is to compare the secondary school mathematics curriculum of Turkey and Indonesia with respect to the paradigm embedded into them. Turkey and Indonesia have very competitive neighbouring countries respectively such as Germany, Netherlands, France and Singapore, Malaysia, China, japan which give them educational challenges and also make some changes in their education systems. Methodologically, this is a comparative study with qualitative approaches. The main data collection tools are the curricula and mathematics textbooks of both countries so that document analysis is the methodological technique to be utilised in this research. The data is analysed by coding and presented by descriptive statistics. In the implementation of education system in both countries, Turkey and Indonesia have run into paradigm transformation which started from behaviourist and then changed to constructivist since 2005 and 2007 respectively. It seems the paradigm in two countries shifted from what to teach to how to teach, however the problem is preparedness for the policies and the related situations. We argue that Turkish and Indonesian governments may use the similarities and differences in the comparison for the sake of the need for improving the quality of education in the two countries. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: comparative education; Turkish education system; Indonesian education system; secondary mathematics curriculum; paradigms